IMPLEMENTASI PERMAINAN TRADISIONAL BAKIAK DALAM MENINGKATKAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR NEGERI WIROKERTEN - Giraldi Eka Saputra; Suyitno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Traditional games are an integral part of Indonesia’s cultural heritage and possess significant educational value, particularly in fostering students’ character development. This study focuses on the implementation of the traditional Bakiak game as a medium for strengthening character education among elementary school students. The research was motivated by the declining popularity of traditional games among students, which has led to concerns about the loss of character-building opportunities embedded in such activities.This qualitative research employed a descriptive-analytical approach. Data were collected through observation, interviews, and documentation, and analyzed using data collection, reduction, and presentation techniques. The participants consisted of students from SD Negeri Wirokerten.The results indicate that the implementation of the Bakiak game contributes positively to the development of students' character. The activity supports the enhancement of physical and motor skills, fosters cooperation, and nurtures appreciation for individual differences. Supporting factors for implementation include the availability of time, a flexible curriculum, and strong support from the school community and students’ parents. Conversely, inhibiting factors include limited facilities and infrastructure for traditional games and student behaviors that still require development.This study provides empirical evidence on the educational potential of traditional games, offering valuable insights for educators and future researchers in designing relevant and sustainable character education programs.